2011
DOI: 10.1007/s10681-011-0574-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a core set of microsatellite markers for genetic diversity analysis in watermelon, Citrullus lanatus Thunb. Matsum. & Nakai

Abstract: Watermelon, Citrullus lanatus Thunb. Matsum. & Nakai is an important vegetable crop worldwide. Due to its narrow genetic base, detection and utilization of the genetic variations, cultivar identification and increasing genetic diversity are some important tasks for watermelon breeders. Molecular markers, especially microsatellites or simple sequence repeats (SSRs) are playing increasingly important roles for these purposes. In the present study, a core set of 23 highly informative SSR markers was developed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 42 publications
6
35
2
Order By: Relevance
“…In the current study the number of alleles per locus ranged from 2 to 19, with a mean of 9.4. This was higher than the range from 2 to 7 alleles (mean = 3.7) reported by Zhang et al (2012). Jarret et al (1997) reported an average of 4.7 alleles per locus in 32 watermelon accessions which was lower than those observed in the current study.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In the current study the number of alleles per locus ranged from 2 to 19, with a mean of 9.4. This was higher than the range from 2 to 7 alleles (mean = 3.7) reported by Zhang et al (2012). Jarret et al (1997) reported an average of 4.7 alleles per locus in 32 watermelon accessions which was lower than those observed in the current study.…”
Section: Discussioncontrasting
confidence: 93%
“…Dessert watermelon has a narrow genetic base (Levi et al, 2001;Hwang et al, 2011) probably due to many years of domestication and selection for desirable horticultural traits (Levi et al, 2001;Dane and Liu, 2007;Minsart et al, 2011). Therefore, continued search, identification and selection of unique genotypes is important for sustainable production of dessert watermelon (Sheng et al, 2012;Zhang et al, 2012;Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNP and CAPS markers have been routinely used in agricultural breeding programs, plants and animal variation studies, genome mapping and association mapping studies (Kole and Abbott 2008). CAPS markers were proven to be useful for increasing marker resolution in cucurbita crops to identify genes related to plant diseases, but little attention has focused on flesh color markers for watermelon (Femandez-Silva et al 2008;Ling et al 2009;Morales et al 2005;Tezuka et al 2009;Zhang et al 2011). Only one CAPS marker (Phe226) has been identified thus far (Bang et al 2010), which could perfectly co-segregate the flesh color phenotype to distinguish red and canary yellow flesh color.…”
Section: Introductionmentioning
confidence: 99%
“…ISSR [8], SSR [9]- [16], SRAP [11] [17], EST-PCR [18], and HFO-TAG markers [19] have been used to estimate the genetic relationship among cultivated watermelons and different Citrullus species. Studies by [13] and [19] revealed low levels of DNA polymorphism among cultivated watermelons but high genetic diversity among the Citrullus subspecies. [20] and [21] also revealed very low genetic diversity in cultivated watermelon.…”
Section: Introductionmentioning
confidence: 99%